2021
DOI: 10.21608/amj.2021.178501
|View full text |Cite
|
Sign up to set email alerts
|

Direct Trocar Insertion in Gynecological Laparoscopy; A Case Series of 300 Cases

Abstract: Background: Laparoscopy is a diagnostic and surgical procedure used in all surgical disciplines.The rationale for DTI, without prior pneumoperitoneum, is based on the difficulty of grasping and lifting the abdomen after it is distended with gas and the fact that the VN accounts for many complications. It was noted that complications of laparoscopic surgery are mostly entry-related and independent of the complexity of surgery. DTI without pneumoperitoneum was reported to be associated with minimal complications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Both techniques have generally favorable complication profiles. Possible complications for both DTI and VN include surgical site infection, omental injury or extraperitoneal insufflation 11. Recent studies have suggested that DTI is safer and faster than the VN entry technique, but the largest meta analyses to date have not found clinical significance between these two techniques 12–14…”
Section: Introductionmentioning
confidence: 99%
“…Both techniques have generally favorable complication profiles. Possible complications for both DTI and VN include surgical site infection, omental injury or extraperitoneal insufflation 11. Recent studies have suggested that DTI is safer and faster than the VN entry technique, but the largest meta analyses to date have not found clinical significance between these two techniques 12–14…”
Section: Introductionmentioning
confidence: 99%